2021
DOI: 10.2147/ott.s309576
|View full text |Cite
|
Sign up to set email alerts
|

High Matrix Metalloproteinase 28 Expression is Associated with Poor Prognosis in Pancreatic Adenocarcinoma

Abstract: Purpose Pancreatic adenocarcinoma (PAAD) is a devastating disease with high mortality and morbidity. Matrix metalloproteinase 28 (MMP28) has been associated with carcinogenesis of many human cancers. However, little is known about the potential prognostic value and underlying regulatory mechanisms of MMP28 in PAAD. Methods The relationship between MMP28 expression level and various clinicopathological parameters was analyzed in TCGA-PAAD cohorts. MMP28-correlated genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…First, we profiled the expression status of 411 gene transcripts associated with the ECM and cell adhesion (QIAGEN). WT and PKN2 KO PSCs were cultured in complete medium or exposed to TGF-β1 for 72 h. PKN2 deletion predominantly resulted in the upregulation of ECM-associated genes under 2D cell culture conditions ( Figures 2 A and 2B), including genes associated with metastasis (Serpine2, Fmod, Itgbl1, Aspn, MMP28, and Col6a3; Buchholz et al., 2003 ; Liu et al., 2021 ; Wiechec et al., 2021 ). Many of these genes were also differentially expressed (DE) in PKN2 KO PSCs compared with WT PSCs following TGF-β1 stimulation ( Figures 2 B and 2C; Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…First, we profiled the expression status of 411 gene transcripts associated with the ECM and cell adhesion (QIAGEN). WT and PKN2 KO PSCs were cultured in complete medium or exposed to TGF-β1 for 72 h. PKN2 deletion predominantly resulted in the upregulation of ECM-associated genes under 2D cell culture conditions ( Figures 2 A and 2B), including genes associated with metastasis (Serpine2, Fmod, Itgbl1, Aspn, MMP28, and Col6a3; Buchholz et al., 2003 ; Liu et al., 2021 ; Wiechec et al., 2021 ). Many of these genes were also differentially expressed (DE) in PKN2 KO PSCs compared with WT PSCs following TGF-β1 stimulation ( Figures 2 B and 2C; Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…TIME, including innate and adaptive immune cells, extracellular immune factors, and molecules on the cell surface, are critically involved in tumorigenesis (53)(54)(55). Studies have that macrophages, DCs, neutrophils, myeloid suppressor cells, NK cells, innate lymphocytes, and cytokines in TME could interfere with immune function, inhibit anti-tumor immune response mediated by T cells, stimulate angiogenesis, and promote the proliferative, invasive and metastatic ability of cancer cells (56)(57)(58)(59). Our results showed a significant increase in macrophages, resting and activated DCs, as well as activated mast cell infiltration in patients in PANcluster A.…”
Section: Discussionmentioning
confidence: 99%
“…MMPs comprise a family of zinc-dependent endoproteinase, responsible for degrading extracellular matrix components [ 1 ]. Deregulation of the MMPs has been implicated in many aging-related diseases, such as Alzheimer’s disease, Parkinson's disease, age-related macular degeneration, bone diseases and cancers [ 6 , 9 , 11 13 , 15 18 ]. Although biochemical properties of MMPs has been intensively studied, accumulated evidences have shown that our understanding of the MMPs is far from absolute, and some discoveries even have conflicted conclusions with previous findings [ 23 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cancers, occurring mostly in middle age and above, have been linked to MMPs with evidence as they are an important factor promoting tumor progression [ 14 ]. This is especially true for tumors like pancreatic adenocarcinoma, prostate adenocarcinoma, bladder urothelial carcinoma and melanoma, which are commonly at risk above the age of 50 [ 15 18 ]. Collectively they reveal that MMPs widely participate in physiological and pathological processes, and thus are promising targets for diagnosis and drug development of aging-related diseases.…”
Section: Introductionmentioning
confidence: 99%